Consensus on surgical technique for sentinel lymph node dissection in cervical cancer - Bizzarri, Nicolò; Obermair, Andreas; Hsu, Heng-Cheng; Chacon, Enrique; Collins, Anna; Tsibulak, Irina; Mutombo, Alex; Abu-Rustum, Nadeem R; Balaya, Vincent; Buda, Alessandro; Cibula, David; Covens, Allan; et al. (International journal of gynecological cancer, 2024)
OBJECTIVE: The purpose of this study was to establish a consensus on the surgical technique for sentinel lymph node (SLN) dissection in cervical cancer. METHODS: A 26 question survey was emailed to international expert gynecological oncology surgeons. A two-step modified Delphi method was used to establish consensus. After a first round of online survey, the questions were amended and a second round, along with semistructured interviews was performed. Consensus was defined using a 70% cut-off for agreement. RESULTS: Twenty-five of 38 (65.8%) experts responded to the first and second rounds of the online survey. Agreement ≥70% was reached for 13 (50.0%) questions in the first round and for 15 (57.7%) in the final round. Consensus agreement identified 15 recommended, three optional, and five not recommended steps. Experts agreed on the following recommended procedures: use of indocyanine green as a tracer; superficial (with or without deep) injection at 3 and 9 o'clock; injection at the margins of uninvolved mucosa avoiding vaginal fornices; grasping the cervix with forceps only in part of the cervix is free of tumor; use of a minimally invasive approach for SLN biopsy in the case of simple trachelectomy/conization; identification of the ureter, obliterated umbilical artery, and external iliac vessels before SLN excision; commencing the dissection at the level of the uterine artery and continuing laterally; and completing dissection in one hemi-pelvis before proceeding to the contralateral side. Consensus was also reached in recommending against injection at 6 and 12 o'clock, and injection directly into the tumor in cases of the tumor completely replacing the cervix; against removal of nodes through port without protective maneuvers; absence of an ultrastaging protocol; and against modifying tracer concentration at the time of re-injection after mapping failure. CONCLUSION: Recommended, optional, and not recommended steps of SLN dissection in cervical cancer have been identified based on consensus among international experts. These represent a surgical guide that may be used by surgeons in clinical trials and for quality assurance in routine practice.
Keywords: Consensus; Indocyanine Green; Sentinel Lymph Node Biopsy; konsensus; indokyanová zeleň; lymfatické metastázy; Lymph Nodes; nádory děložního čípku; Lymphatic Metastasis; ženské pohlaví; Lymph Node Excision; Humans; Sentinel Lymph Node; lymfadenektomie; lymfatické uzliny; Uterine Cervical Neoplasms; biopsie sentinelové lymfatické uzliny; Female; Cervical Cancer; Laparoscopes; lidé